Characteristic flavor formation of thermally processed N-(1-deoxy-α-d-ribulos-1-yl)-glycine: Decisive role of additional amino acids and promotional effect of glyoxal. (1st March 2022) - Zhan, Huan; Cui, Heping; Yu, Junhe; Hayat, Khizar; Wu, Xian; Zhang, Xiaoming; Ho, Chi-Tang
Highlights: Added glycine boosts the diversity of furans via formaldehyde in chain elongation. Added glutamic acid or lysine promote pyrazine formation by nucleophilic attack. Glyoxal promoted the degradation of ARP and retro-aldol cleavage of deoxyosone. Abstract: The role of amino acids and α-dicarbonyls in the flavor formation of Amadori rearrangement product (ARP) during thermal processing was investigated. Comparisons of the volatile compounds and their concentrations when N -(1-deoxy-α-d -ribulos-1-yl)-glycine reacted with different amino acids or glyoxal (GO) at 100 °C were executed. Additional amino acids, such as glycine (Gly), in ARP models contributed to the diversity of furanoids by the chain elongation of the derived formaldehyde. Whereas the monoanion of additional glutamic acid acted as nucleophile, favored 2-ethyl-3, 5-dimethylpyrazine and 2, 5-dimethylpyrazine formation; the nonionized amino group of additional lysine were involved in α-dicarbonyls formation, causing pyrazine and methylpyrazine accumulation in the ARP model. Moreover, the high dosage and pH stabilization of additional GO probably promoted the ARP degradation and deoxyosones retro-aldol cleavage, resulting in methylpyrazine rather than furanoids formation. The present work provided the guidance for the controlled flavor formation of ARP in industrial application.